Cover Image, Volume 176A, Number 11, November 2018. Issue 11 (8th December 2018) - Burren, Christine P.; Caswell, Richard; Castle, Bruce; Welch, C. Ross; Hilliard, Tom N.; Smithson, Sarah F.; Ellard, Sian
Abstract : The cover image is based on the Research Article First data from a parent‐reported registry of 81 individuals with Coffin–Siris syndrome: Natural history and management recommendations by Elizabeth A. Mannino et al., DOI:10.1002/ajmg.a.40471 .